2004
DOI: 10.1016/j.electacta.2003.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical noise and impedance study of aluminium in weakly acid chloride solution

Abstract: The electrochemical noise (EN) characteristics of pure aluminium in unbuffered potassium chloride solution and with acetic acid/sodium acetate buffer at pH 5.4 and 4.3 have been analysed to throw light on the influence of pH and of the presence of buffer at the aluminium surface on chloride ion-induced corrosion. Comparison has been made with results obtained by electrochemical impedance spectroscopy (EIS) and quantitative deductions made concerning the values of the noise resistance and the magnitude of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 41 publications
1
25
1
Order By: Relevance
“…From the relative current of the two peaks (peaks 1 and 2 of Figures 3(a) and 3(b)), it could be concluded that at higher polarization potential copper preferably dissolved as soluble Cu(II) soluble species and the proportion of formation of soluble Cu(I) species was reduced. The literature's [38][39][40][41] reports about the mechanism of dissolution of copper in aqueous solution agreed well with the present observation from RRDE measurements.…”
Section: Rotating Ring-disc Electrode Studysupporting
confidence: 81%
“…From the relative current of the two peaks (peaks 1 and 2 of Figures 3(a) and 3(b)), it could be concluded that at higher polarization potential copper preferably dissolved as soluble Cu(II) soluble species and the proportion of formation of soluble Cu(I) species was reduced. The literature's [38][39][40][41] reports about the mechanism of dissolution of copper in aqueous solution agreed well with the present observation from RRDE measurements.…”
Section: Rotating Ring-disc Electrode Studysupporting
confidence: 81%
“…This problem in case of Al-based metal matrix composite is due to the formation of stable tenacious oxide film, resulting in poor wettability with the ceramic particle. One of the common practices to improve wettability of an Al melt is through addition of small amount of reactive metals like magnesium and titanium prior to the incorporation of ceramic particle [1,3]. However, in the present work, 4…”
Section: Introductioncontrasting
confidence: 44%
“…The major limitation in many cases in fabricating metal matrix composites by liquid phase route resides upon the incompatibility of the reinforcement and the matrix [1][2][3]. This problem in case of Al-based metal matrix composite is due to the formation of stable tenacious oxide film, resulting in poor wettability with the ceramic particle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 90ties a preponderant importance has been given to the study of this phenomenon to explain the dynamics and mechanisms of the electrochemical processes taking place in the electrified interface (Gouveia-Caridade et al, 2004;Kearns et al, 1996;García-Ochoa et al, 1996;Hladky & Dawson, 1980;Loto & Cottis, 1987).…”
Section: Fig 7 Dlepr Curves Obtained From 304 Ss Samples At the Hazmentioning
confidence: 99%